2012
DOI: 10.3171/2012.1.focus11340
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neuropsychological outcome after resection of temporal and extratemporal seizure foci

Abstract: Resection of seizure foci is an effective treatment for the control of medically intractable epilepsy. However, cognitive morbidity can occur as a result of surgical intervention. This morbidity is dependent on several factors, including location and extent of resection, disease characteristics, patient demographic characteristics, and functional status of the tissue to be resected. In this review article, the authors provide a summary of the neurocognitive outcomes of epilepsy surgery with an emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…Quantitative measurement revealed smaller presurgical CC area in patients with treatment‐resistant epilepsy (TRE), relative to controls, after controlling for overall brain volume. Variation in CC area was associated with pre‐ to postsurgical change in working memory, after controlling for established predictors of cognitive outcome, such as age and level of cognitive functioning . This was not the case for longer‐term retention of verbal information; there was no relationship between CC area and pre‐ to postsurgical change in delayed verbal memory.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Quantitative measurement revealed smaller presurgical CC area in patients with treatment‐resistant epilepsy (TRE), relative to controls, after controlling for overall brain volume. Variation in CC area was associated with pre‐ to postsurgical change in working memory, after controlling for established predictors of cognitive outcome, such as age and level of cognitive functioning . This was not the case for longer‐term retention of verbal information; there was no relationship between CC area and pre‐ to postsurgical change in delayed verbal memory.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, postsurgical gains in executive domains such as attention and working memory can be observed . Clinical (e.g., epilepsy duration, presurgical cognitive level) and demographic (e.g., age) factors predict postsurgical cognitive outcomes . Yet, little is known about the degree to which cross‐hemispheric white matter pathways promote recovery of cognitive functions following epilepsy surgery.…”
mentioning
confidence: 99%
“…Similar findings had been published previously [16,17,19]. Our findings are consistent with already reported verbal memory deterioration following dominant temporal lobe surgery [7,18,19,20].…”
Section: Discussionsupporting
confidence: 82%
“…3). Functional connectivity studies of the language deficits known to be present in TLE have emerged (for review of language deficits see [39,40]). Pravata et al [35] showed that for both left 2.5 R 4 FIGURE 2.…”
Section: Anticorrelated Activity Correlated Activitymentioning
confidence: 99%